Migration as Prophecy Fulfilled: The Case of Hadiya Migration from Southern Ethiopia to South Africa - Dereje Feyissa Dori (African Human Mobility Review)
This article examines the role religion has played in the process of Hadiya migration from southern Ethiopia to South Africa—from decision making to processes of settlement at destination. Religion, specifically evangelical Christianity, has played a key role in the various phases of the migration process: from imagination of a sacred destination, signification of migration as a gift of God, risk perception and negotiation through to place making and spiritual engagements to overcome specific challenges of the new migration habitus. The article situates migration processes within a broader historical context and explains how spiritually animated migratory agency has helped Hadiya migrants negotiate the historically shaped regional inequality within Ethiopia. It concludes with an emphasis on how the Hadiya migration story ethnographically demonstrates the crucial role religion plays in migration processes, with a call for migration studies to take seriously intangible factors in migration.